KRITIK SOSIAL TEATER EPIK DALAM STRUKTUR LAKON TUK KARYA BAMBANG WIDOYO SP - Hudha, Tafsir (Acintya, 2009)
A study of epic theory and its aplication (social realism) is an attempt to search a set and several epic methods which invented through the Tuk’s plays of Bambang Widoyo SP creation. This article will begin from a study of epic theater and its existence generally and its point of view related to social condition which inspires and pointed its audience either. This article traces and focuss on both the relation and its impacts among social realities and theater expression, and its relation to validity of the social realism’s theories (epic theories) in the theater. According to this article, the Tuk’s play of Bambang Widoyo’s creation will be analyzed from its structure of Tuk’s plays itself and its texture. By the end of this article, the Tuk’s plays of Bambang Widoyo’s creation may inspires the audiences through its tracing’s attemption of epic theory in the plays itself.Keyword : epic theory, theater, social criticism, structure, texture